Pengaruh Tingkat Pendapatan dan Tarif Pajak terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Air Permukaan di Kabupaten Bekasi Tahun 2022 - Jessika J. Doloksaribu; Ratih Kumala (Jurnal Ilmu Administrasi Publik, 2023)
Tax is a manifestation of the dedication and participation of taxpayers directly and jointly carrying out tax obligations in the framework   of  state  financing  and  national  development. According to Aurelija Anciūtė & Rūta Kropienė, tax compliance is influenced by four variables, namely income level, tax rate, audit probability, and penalty rate. This study aims to determine the effect of income levels and tax rates on taxpayer compliance in paying surface water tax in Bekasi Regency in 2022. The data collection method used in this research was a questionnaire, and the analysis used in this study was quantitative analysis. The results of this study are that the level of income affects taxpayer compliance in paying surface water taxes in Bekasi district in 2022. This is evidenced by the statistical results of the t test for the variable physical evidence being accepted because the tcount > ttable is where 11.350 > 1.960 and the significance value obtained is 0.001 smaller than the value α = 0.05. Tax rates have no effect on taxpayer compliance in paying surface water tax in Bekasi district in 2022. This is evidenced by the statistical results of the t test for the physical evidence variable with the hypothesis not being accepted because the tcount value < ttable where 0.644 < 1.960 and the significance value obtained is 0.520 is greater than the value α = 0.05.. Level of income  and  tax  rates  together  have  a  significant  effect  on taxpayer compliance in paying surface water tax in Bekasi district in 2022. This is evidenced by the statistical value of Fcount 181,797 which is greater than Ftable 2.64, so it can be concluded that the independent variable Level Income (X₁), Tax Rates (X₂) simultaneously have a significant effect on the dependent variable of taxpayer compliance (Y).